An attempt to determine the absolute geomagnetic field intensity in Southwestern Iceland during the Gauss–Matuyama reversal (Dataset) ... - Avto Goguitchaichvili; Prévot, Michel; Thompson, John; Roberts, Neil (Magnetics Information Consortium (MagIC), 2020)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: An attempt to determine the absolute geomagnetic field intensity in Southwestern Iceland during the Gauss–Matuyama reversal ...